واقع إدارة التغيير لدى مديري المدارس في منطقة القصيم التعليمية و الصعوبات التي تواجههم عند تطبيقها - الصالحي، خالد بن سليمان صالح (جامعة القصيم, 2012)
هدفت الدراسة إلى التعرف على واقع إدارة التغيير لدى مديري المدارس في منطقة القصيم التعليمية، وكذلك التعرف على الصعوبات التي تواجههم عند التطبيق، والتعرف على الفروق ذات الدلالة الإحصائية بين أفرد عينة الدراسة ومتغيرات الدراسة (المرحلة، الوظيفة)، وقد استخدام الباحث المنهج الوصفي التحليلي في الدراسة، والاستبانة أداة لجمع المعلومات، وتكونت عينة الدراسة من (378) مديراً، و (324) وكيل مدرسة، و(1492) معلماً، من مختلف المراحل الدراسية الثلاث، وأبرز ما توصلت إليه الدراسة أن واقع إدارة التغيير لدى مديري المدارس يمارس بدرجة كبيرة بمتوسط حسابي قدره (3.18) من (5)، كما أن أكثر الصعوبات التي تواجه مديري المدارس عند تطبيق إدارة التغيير هي: الأعباء المالية التي تتطلبها عملية التغيير، وكثرة الأعباء وضغوط العمل على مديري المدارس، وقلة مساهمة المجتمع المحلي في دعم ومشاركة أنشطة وبرامج المدرسة، وأكدت الدراسة أن هناك فروقاً دالة إحصائية عند مستوى 0.05 بين مديري المدارس والوكلاء والمعلمين حول واقع التطبيق وذلك لصالح مديري المدارس، كما أكدت الدراسة أن هناك فروقاً دالة إحصائياً عند مستوى 0.05 بين مديري المدارس والوكلاء والمعلمين حول معوقات التطبيق وذلك لصالح وكلاء المدارس، كما قدم الباحث عدد من التوصيات والمقترحات. The study aimed to identify the reality of change management among school Principals in educational region of Al-Qassim, as well as to identify the difficulties they face in practice, and to identify the differences of statistical significance between singled out the study sample and variables of the study (Level, Position). \ The study usedt descriptive analytical method, as well as the questionnaire tool to gather information. \ The study sample consisted of (378), and (324) principal and an assistant school principal, and (1492) teachers from different three grades, and highlighted findings of study: That the reality of change management for school principals applies largely \ With average (3.18) out of (5), the more the difficulties faced by school principals when the application of change management are: The financial burden required by the change process, and the large burden and of work stress on school a principals, and the lack of contribution and support from local community, participation of activities and programs of the school, the study confirmed that there are differences statistically significant at the level of (0.05) between principals and assistant school principal, and teachers about the reality of the application for the benefit of school administrators, as confirmed by the study that there are differences statistically significant at the level of 0.05 between principals and assistant school principal, and teachers about the obstacles to the application for the benefit of assistant school principal, also researcher developed some of recommendations and suggestions.
778591
Keywords: السعودية -- الإدارة المدرسية -- إدارة التغيير -- مديرو المدارس -- الدراسات الإحصائية -- القصيم -- التخطيط الإداري -- التنظيم الإداري -- النظم التعليمية